Swine as reservoirs of zoonotic borderline oxacillin-resistant Staphylococcus aureus ST398 - Santos, S. C.L.; Saraiva, M. M.S. [UNESP]; Moreira Filho, A. L.B.; Silva, N. M.V.; De Leon, C. M.G.; Pascoal, L. A.F.; Givisiez, P. E.N.; Gebreyes, W. A.; Oliveira, C. J.B. (Elsevier, 2021)
Methicillin resistance mediated by the mecA gene in Staphylococcus aureus, also known as “true MRSA”, is typically associated with high oxacillin MIC values (≥8 mg/L). Because non-mecA-mediated oxacillin resistant S. aureus phenotypes can also cause hard-to-treat diseases in humans, their misidentification as methicillin-susceptible S. aureus strains (MSSA) can compromise the efficiency of the antimicrobial therapy. These strains have been refereed as Borderline Oxacillin-Resistant S. aureus (BORSA) but their characterization and role in clinical microbiology have been neglected. Considering the increasing importance of livestock-associated methicillin-resistant S. aureus ST398 (LA-MRSA) as an emerging zoonotic pathogen worldwide, this study aimed to report the genomic context of oxacillin resistance in porcine S. aureus ST398 strains. S. aureus isolates were recovered from asymptomatic pigs from three herds. Oxacillin MIC values ranged from 4 to 32 mg/L. MALDI-TOF-confirmed isolates were screened for mecA and mecC by PCR and genotyped by means of PFGE and Rep-PCR. Seven isolates were whole genome sequenced. None of the isolates harbored the mecA gene or its variants. Although all seven sequenced isolates belonged to one sequence type (ST398), two different spa types (t571 and t1471) were identified. All isolates harbored conserved blaZ gene operon and no mutations on genes encoding for penicillin-binding-proteins were detected. Genes conferring resistance against other drugs such as aminoglycosides, chloramphenicol, macrolide, lincosamide and streptogramin (MLS), tetracycline and trimethoprim were also detected. Isolates also harbored virulence genes encoding for adhesins (icaA; icaB; icaC; icaD; icaR), toxins (hlgA; hlgB; hlgC; luk-PV) and protease (aur). Pigs can serve as reservoirs of non-mecA-mediated oxacillin-resistant ST398 strains potentially pathogenic to humans. Considering that mecA has been the main target to screen methicillin-resistant staphylococci, the occurrence of BORSA phenotypes is probably underestimated in livestock.
Keywords: Antimcirobial resistance; blaZ; mec; Methicillin; Pigs